The invincible Duff Green Whig of the West - Belko, W. Stephen, 1967- (University of Missouri Press, 2006)
"Drawing on previously unexploited primary sources, Belko illuminates the wide-ranging influence of Duff Green as land speculator, entrepreneur, lawyer, militia officer, politician, and newspaper editor. Disputing common assumption, Green is portrayed as a political moderate and independent westerner who played a fundamental role in the shaping of Jacksonian America"--Provided by publisher.